Labor Scarcity, Technology Adoption and Innovation: Evidence from the Cholera Pandemics in 19th Century France - Raphaël Franck (Center for Economic Studies and ifo Institute (CESifo), 2022)
To analyze the impact of labor scarcity on technology adoption and innovation, this study uses the differential spread of cholera across France in 1832, 1849 and 1854, before the transmission mode of this disease was understood. The results suggest that a larger share of cholera deaths in the population, which can be causally linked to summer temperature levels, had a positive and significant shortrun effect on technology adoption and innovation in agriculture but a negative and significant short-run impact on technology adoption in industry. These results, which are not driven by migration, urbanization, religiosity or local financial intermediation, can be explained by the positive impact of labor scarcity on human capital formation.
Keywords: I15; N13; O33; 330; epidemics; labor scarcity; technology adoption